Fiscal stabilizations: When do they work and why - Silvia Ardagna (Wellesley College, Department of Economics, 2002)
This paper studies the determinants and chaIlllels through which fiscal contractions influence the dynamics of the debt-to-GDP ratio and GDP growth. Using data from a panel of OECD countries, the paper shows that the success of fiscal adjustments in decreasing the debt-to-GDP ratio depends on the size of the fiscal contraction and less on its composition. The rate of growth of output matters too, but higher GDP growth does not drive the success of a fiscal stabilization. In contrast, whether a fiscal adjustment is expansionary depends largely on the composition of the fiscal manoeuvre. In particular, stabilizations implemented by cutting public spending lead to higher GDP growth rates. The effects of the composition on growth work mostly through the labor market rather than through agents' expectations of future fiscal policy. Finally, the evidence suggests that successful and expansionary fiscal contractions are not the result of accompanying expansionary monetary policy or exchange rate devaluations.
Keywords: 330; Finanzpolitik; Öffentliche Ausgaben; Wirtschaftswachstum; OECD-Staaten